The Roman Catholic Church and the United Church of Zambia challenged by HIV and AIDS, which results in creating poverty among Zambian people - Masango, Maake J.S (University of Pretoria, 2013)
Dissertation (MA (Practical Theology))--University of Pretoria, 2006.